Pengaruh Daya Ledak Tungkai, Keseimbangan, Dan Persepsi Kinestetik Terhadap Kecepatan Tendangan Mawashi Geri Dalam Cabang Olahraga Karate Pada Karateka Dojo Kostrad Kariango. - Syamsiah, Syamsiah; Ihsan, Andi; Jamaluddin, Jamaluddin; Juhanis, Juhanis; Hudain, Muh. Adnan (Prodi Pendidikan Jasmani dan Olahraga, 2025)
This study is descriptive research, the processing of the hypothesis using path analysis. In this research design, the research subjects were taken by random sampling, the population of this study were 33 Kariango Kostrad Karate Dojo karate athletes, the research sample was 15 Kariango Kostrad Karate Dojo karate athletes. Based on the results of the data analysis, this study concludes that: (1). There is a significant influence of leg explosive power on kinesthetic perception in the karate sport branch of karate athletes at the Kariango Kostrad Dojo with a ρ value of = 0.308 (PValue < 0.05); (2). There is a significant influence of balance on kinesthetic perception in the karate sport branch of karate athletes at the Kariango Kostrad Dojo with a ρ value of = 0.394 (PValue < 0.05); (3). There is a significant influence of leg explosive power on the speed of the Mawashi geri kick in the karate sport branch of karate athletes at the Kariango Kostrad Dojo with a ρ value of = 0.163 (PValue < 0.05); (4). There is a significant influence of balance on the speed of the Mawashi geri kick in the karate sport branch of karate athletes at the Kariango Kostrad Dojo with a ρ value of = 0.827 (PValue < 0.05); (5). There is a significant influence of kinesthetic perception on the speed of the Mawshi geri kick in the karate sport branch at the Kariango Kostrad Dojo karate athletes with a ρ value of = 0.418 (PValue < 0.05); (6). There is an indirect influence of leg explosive power on the speed of the Mawashi geri kick through kinesthetic perception in the karate sport branch at the Kariango Kostrad Dojo karate athletes with a ρ value of = 0.284 (PValue < 0.05); (7). There is an indirect influence of balance on the speed of the Mawashi geri kick through kinesthetic perception in the karate sport branch at the Kariango Kostrad Dojo karate athletes with a ρ value of = -0.0287 (PValue < 0.05).